Pengaruh Mekanisme Corporate Governance Terhadap Akuntabilitas Laporan Keuangan Pemerintah Daerah - Aziza Istiqamah; Inggit Kumorojati; Selika Rahma Raidatulah (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study examines how corporate governance practices affect local government financial reports' accountability. Transparency and accountability in local government financial management are thought to be improved by good corporate governance. The findings demonstrate that corporate governance practices have a favorable impact on the caliber of financial reports produced by local governments. These results emphasize how crucial it is to put good governance concepts into practice in order to promote accountability in the financial management of local governments.